Hubungan Antara Indeks Massa Tubuh Dengan Kelincahan Dan Volume Oksigen Maksimum Pada Pemain Futsal Mufc Karanganyar - Untoro, Fajar Setyo, Dwi Kurniawati, SSt.FT (2017)
Background: Futsal is a version of the game of football in a room that is recognized by an international body of football smaller size and with a player less, futsal game are more likely dynamic and requires endurance cardiopulmonary prime and agility of the players, other than that height and weight factors greatly affect the achievement of futsal. Of the 86 populations found 9 people are over weight and most of them within ideal limits and under wight at MU Fans Club Karanganyar. Objective: This study aimed to determine the relationship of the body mass index of the agility futsal players and to determine the relationship of the body mass index to maximum volume of oxygen futsal players. Methods: This study is observational analytic study with cross sectional approach. Analytic observational study, which is to find the relationship between independent variables and the dependent variable analysis to determine whether there is any relationship between variables that need to be developed hypothesis. The samples using purposive sampling method that meets the criteria inklusi and exclusion. Total sample study were 30 futsal players MU fans Club Karanganyar. Results: The data were normally distributed, statistical test to test the effect of using the Pearson Test result that the value sig (p) IMT with the agility that is 0,018 while the value sig (p) IMT with VO2max is 0.042. Conclusion: Based on these data we can conclude that There is a relationship between body mass index with agility a in futsal players karanganyar. And there is a relationship between the body mass index to maximum volume of oxygen in futsal players MUFC karanganyar.